Perinatal Parenting Stress, Anxiety, and Depression Outcomes in First-Time Mothers and Fathers: A 3- to 6-Months Postpartum Follow-Up Study - Vismara, Laura; Rollè, Luca; Agostini, Francesca; Sechi, Cristina; Fenaroli, Valentina; Molgora, Sara; Neri, Erica; Prino, Laura E.; Odorisio, Flaminia; Trovato, Annamaria; Polizzi, Concetta; Brustia, Piera; et al. (Frontiers in Psychology, 2016)
Objective: Although there is an established link between parenting stress, postnatal depression, and anxiety, no study has yet investigated this link in first-time parental couples. The specific aims of this study were 1) to investigate whether there were any differences between first-time fathers’ and mothers’ postnatal parenting stress, anxiety, and depression symptoms and to see their evolution between three and 6 months after their child’s birth; and 2) to explore how each parent’s parenting stress and anxiety levels and the anxiety levels and depressive symptoms of their partners contributed to parental postnatal depression. Method: The sample included 362 parents (181 couples; mothers’ MAge = 35.03, SD = 4.7; fathers’ MAge = 37.9, SD = 5.6) of healthy babies. At three (T1) and 6 months (T2) postpartum, both parents filled out, in a counterbalanced order, the Parenting Stress Index-Short Form, the Edinburgh Postnatal Depression Scale, and the State-Trait Anxiety Inventory. Results: The analyses showed that compared to fathers, mothers reported higher scores on postpartum anxiety, depression, and parenting stress. The scores for all measures for both mothers and fathers decreased from T1 to T2. However, a path analysis suggested that the persistence of both maternal and paternal postnatal depression was directly influenced by the parent’s own levels of anxiety and parenting stress and by the presence of depression in his/her partner. Discussion: This study highlights the relevant impact and effects of both maternal and paternal stress, anxiety, and depression symptoms during the transition to parenthood. Therefore, to provide efficacious, targeted, early interventions, perinatal screening should be directed at both parents.